Effects of audit committee attributes and corporate board activity on earnings quality of quoted consumer goods companies in Nigeria - Salawu, Mary Kehinde; Oyetunji, Gafar Tunde; Ololade, Babatunde (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
Purpose: The study examined the effect of audit committee attributes and corporate board activity on earnings quality of listed consumer goods companies. Also, the effect of pooled audit committee attributes using principal component analysis and board activity was examined on earnings quality. Methodology: The study population was twenty-four listed consumer goods companies, while a sample of seventeen firms was purposively selected. Secondary data obtained from annual reports of the sample firms was analysed using both random and fixed effects. Results and Conclusion: Results showed that the audit committee’s financial literacy and expertise in audit and accounting have a significant negative effect on earning quality, while other audit committee attributes showed insignificant effects. Also, board size and leverage have negative significant effects on earnings quality. Furthermore, the results of the pooled audit committee’s attributes show an insignificant positive effect on earnings quality, while board size and board meetings have a significant negative effect on earnings quality. The study concludes that audit committee members with financial literacy, board size, and frequency of audit committee meetings reduce management tendencies to manage earnings. Implication: The practical implication of the study’s findings is that members of the audit committee who are financially literate and the size of the audit committee members have the potential to dissuade management from opportunistic behaviour.